Road soft foundation rapid reinforcement anti-skid construction process
By using integrated drainage and grouting micro-pile pipes, dual-channel grouting technology, and steel fiber reinforced concrete materials with high-polymer early-strength anti-mud and water-reducing agents, the problems of lateral slippage and grout dilution in soft soil foundation reinforcement were solved, achieving rapid reinforcement and early strength establishment, and improving the construction efficiency and stability of roads.
Patent Information
- Application Number
- CN202611237821.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-11-06
AI Technical Summary
Existing road soft soil reinforcement techniques are difficult to effectively restrain the lateral slippage of biased strata, the grouting fluid in water-rich environments is easily washed away and diluted by groundwater, and the pavement repair materials have poor mud resistance and slow early strength development, resulting in excessively long construction cycles.
The system employs integrated drainage and grouting micropile pipes and a dual-channel grouting process, combining vertical and inclined piles to construct a spatial bearing matrix. It uses steel fiber reinforced concrete material with high-polymer early-strength anti-mud water-reducing agent, and discharges free ground water through the drainage section of the micropile pipe to ensure the retention rate of grout in a dynamic water environment. The high-polymer water-reducing agent is used to accelerate the early hydration of concrete, forming a rapidly reinforced pavement structure.
It effectively restrains lateral slippage of soft soil foundations, improves the overall structural mechanical stability of the roadbed, reduces grout dilution, shortens the road closure and repair cycle, and meets the needs of rapid construction and early opening to traffic.
Smart Images

Figure CN123043820A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of road infrastructure engineering technology, specifically to a rapid reinforcement and anti-skid construction process for soft soil foundations. Background Technology
[0002] In the construction and maintenance of transportation infrastructure, road engineering often faces complex soft soil foundation environments such as coastal areas, riverside areas, or areas with high groundwater levels. These soft soil foundations typically have characteristics such as high water content, low shear strength, and high compressibility, making them prone to deformation and damage under long-term traffic loads. Therefore, targeted foundation reinforcement is required in the repair of road defects.
[0003] Currently, in soft soil foundation treatment, conventional vertical pile foundations or replacement techniques mainly focus on improving the vertical bearing capacity of the foundation. When facing eccentric terrain or water-rich strata, the foundation not only experiences vertical settlement but also suffers from significant horizontal earth pressure. Traditional vertical reinforcement structures have limited lateral deformation stiffness and are difficult to effectively restrain the lateral slippage of weak soil layers.
[0004] The foundation and the overlying pavement structure are often subjected to separate stresses, lacking a coordinated transmission mechanism, which can easily induce overall road instability under long-term dynamic loads. In the underground reinforcement grouting process, water-rich strata contain high pore water pressure and groundwater flow. Conventional grouting techniques often use grout with a long initial setting time for direct injection. Under the scouring of groundwater, the grout is easily diluted and lost, leading to a decrease in the grout's compaction and bonding effect on the soil, and ultimately, the strength of the solidified body is difficult to meet standards.
[0005] During the road structure restoration phase after reinforcement, the construction site environment is complex and often accompanied by soil disturbance. Conventional water-reducing agents used in ordinary concrete are easily adsorbed by clay minerals, causing slump loss and reduced workability of the concrete mixture. Furthermore, traditional road concrete materials have a slow early hydration rate and require a long curing period after pouring, which cannot meet the actual engineering needs of rapid construction and early reopening of traffic to damaged road sections. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides a rapid reinforcement and anti-skid construction process for soft soil foundations, which solves the problems of existing soft soil foundation reinforcement processes being unable to effectively restrain the lateral slippage of biased strata, the easy erosion and dilution of grouting fluid by groundwater in water-rich environments, and the poor mud resistance and slow early strength development of pavement repair materials leading to excessively long road closure construction periods.
[0007] To achieve the above objectives, the present invention provides the following technical solution:
[0008] The first aspect of this invention provides a rapid reinforcement and anti-skid construction process for soft soil foundations, comprising the following steps:
[0009] Detect damaged road sections, define the depth and extent of the weak layer, cut joints along the boundary and mill the old pavement structure layer in layers to expose the soft soil foundation;
[0010] The prefabricated integrated drainage and grouting micro-pile pipe consists of an inner pipe and an outer pipe coaxially sleeved together. The lower part is the drainage section and the upper part is the grouting section. The annular space between the inner pipe and the outer pipe in the grouting section forms the A-component grout delivery channel, and the inner cavity of the inner pipe is the B-component grout delivery channel. The two channels converge in the mixing chamber at the grout outlet of the grouting section.
[0011] Micropile tubes are implanted into the soft soil foundation to form a spatial matrix. The micropile tubes include vertical piles and inclined piles. The inclined piles are all pointed in the direction of lateral slippage of the roadbed. The bottom of the pile penetrates the silt layer and is embedded 0.5m into the bearing layer. After implantation, the piles are left to stand for 2 hours and the free water in the stratum is discharged through the drainage section.
[0012] The A component slurry and the B component slurry are pumped to the A component slurry delivery channel and the B component slurry delivery channel respectively. After the two slurries meet in the mixing chamber, they are injected into the soil through a one-way rubber sleeve valve to form a reinforced and consolidated body.
[0013] Clean the top of the pile pipe and tighten the disc-shaped steel anchor head. Spread and compact graded crushed stone, lay galvanized welded steel mesh and tie it to the steel anchor head and lock it in place. Then pour early-strength steel fiber concrete.
[0014] Preferably, the bottom of the micropile is closed and conical, and the lower 3.0m of the pipe body is the drainage section. The outer pipe wall of the drainage section has plum blossom-shaped holes with a diameter of 8mm, and the inside of the outer pipe is filled with coarse sand filter material.
[0015] The upper part of the pipe body is the grouting section. The outer pipe wall of the grouting section has grout outlet holes with a diameter of 10mm. Each grout outlet hole is covered with a one-way rubber sleeve valve.
[0016] Preferably, the piles are arranged in a spatial matrix with a vertical pile spacing of 1.5m × 1.5m, and the inclined piles are interspersed among the vertical piles. The insertion angle of the inclined piles is 45° to 70° with the horizontal plane.
[0017] Preferably, high-pressure air is introduced into the A-component slurry delivery channel and the B-component slurry delivery channel before pumping the slurry to drain the accumulated water;
[0018] The A component grout and the B component grout are pumped independently at a volume ratio of 1:0.8 to 1:1.2, with the pumping pressure set at 20MPa to 30MPa. Grouting is stopped when the grouting pressure reaches the set pressure and stabilizes for 10 seconds.
[0019] Preferably, the raw materials for component A slurry include, by mass parts:
[0020] 100 parts of ultrafine silicate cement;
[0021] 80-120 parts deionized water;
[0022] Sodium-based bentonite 2.0-5.0 parts;
[0023] Sodium polynaphthalene sulfonate 0.5-1.2 parts;
[0024] It was prepared by mixing at 1500 rpm to 2000 rpm for 15 min to 25 min using a high-shear dispersing emulsifier;
[0025] The B component slurry is liquid sodium silicate diluted with water to 30Be' to 38Be'.
[0026] Preferably, the raw material mix ratio per cubic meter of the early-strength steel fiber concrete is:
[0027] P.O42.5 grade ordinary Portland cement 420~480kg;
[0028] Coarse aggregate 1050~1100kg;
[0029] Fine aggregate 650~700kg;
[0030] 30-45 kg of hook-type galvanized steel fiber;
[0031] High-molecular-weight early-strength anti-mud water-reducing agent: 1.2–1.5 kg;
[0032] Mixing water: 140–160 kg;
[0033] The weight of the polymeric early-strength anti-mud water-reducing agent is calculated based on its dry solids content.
[0034] Preferably, the raw materials of the polymeric early-strength anti-mud water-reducing agent include, by mass parts:
[0035] 100 parts of isopentenyl alcohol polyoxyethylene ether;
[0036] Acrylic acid 8.0-12.0 parts;
[0037] 3.0-6.0 parts of 2-acrylamido-2-methylpropanesulfonic acid;
[0038] 1.0-1.5 parts of ammonium persulfate;
[0039] Mercaptopropionic acid 0.3-0.6 parts;
[0040] Triethanolamine 2.0-4.0 parts.
[0041] Preferably, the polymeric early-strength anti-mud water-reducing agent is prepared through the following steps:
[0042] Add 100 parts of isopentenyl alcohol polyoxyethylene ether and 80 parts of deionized water to a reaction vessel, and stir at 60℃~65℃ and 60rpm~90rpm until completely dissolved to obtain the initial reaction base liquid.
[0043] Solution A is prepared by dissolving acrylic acid and 2-acrylamido-2-methylpropanesulfonic acid in 30-50 parts of deionized water, and solution B is prepared by dissolving ammonium persulfate and mercaptopropionic acid in 30-50 parts of deionized water. Solution A and solution B are added dropwise at a uniform rate at 60℃~65℃ with continuous stirring. The dropwise addition time of solution A is 150min~180min, and the dropwise addition time of solution B is 180min~210min.
[0044] After both solutions A and B have been added, keep the mixture warm for 60 to 90 minutes to allow it to mature.
[0045] Cool to 35°C, add triethanolamine and react for 30 min with continuous stirring. Slowly add 30.0 wt% sodium hydroxide aqueous solution to adjust the pH to 6.0-7.0, and add deionized water to adjust the solid content to 40.0 wt%.
[0046] Preferably, the spreading and compacting of graded crushed stone, laying galvanized welded steel mesh and binding and locking it with steel anchor heads specifically includes:
[0047] Spread and compact 10cm thick graded crushed stone, then lay biaxially stretched HDPE geogrid and galvanized welded steel mesh in sequence, and use U-shaped clips to tie and lock the galvanized welded steel mesh to the disc-shaped steel anchor head.
[0048] Preferably, the process of detecting damaged road sections, defining the depth and extent of the weak layer, and cutting joints along the boundaries and milling the old pavement structure layer in layers specifically includes:
[0049] Ground penetrating radar and portable dynamic penetrating probes were used to detect the damaged road sections, define the depth and extent of the weak layer, and mark the boundaries on the road surface.
[0050] A hydraulic circular saw was used to cut along the boundary, and a mini cold milling machine was used to mill the old pavement structure layer with a thickness of 0.6m in layers.
[0051] In summary, the present invention has at least one of the following beneficial technical effects:
[0052] 1. This invention constructs a spatial bearing matrix in soft soil foundations by setting up vertical micropiles and inclined piles pointing in the direction of slippage. The vertical piles transfer the traffic load from the upper layer to the deep bearing layer to control the vertical settlement of the foundation, while the inclined piles provide tensile and shear stresses in the soil that are opposite to the slippage trend to limit the lateral slippage of the soft soil. Combined with the interlocking and binding of the steel anchor head at the top of the pile with the surface steel mesh and concrete structural layer, a load transmission structure between the deep foundation piles and the surface rigid pavement is formed, which improves the overall structural mechanical stability of the road sections with bias pressure and water-rich soft soil.
[0053] 2. This invention employs an integrated drainage and grouting micro-pile pipe and a dual-channel grouting process to adapt to the underground water-rich stratum environment. After the pile is driven, the drainage section at the bottom of the micro-pile pipe first discharges the free water in the stratum to reduce the pore water pressure. Subsequently, cement-based grout and sodium silicate grout are pumped through independent dual-channel pumps, and they converge in the mixing chamber of the grouting section and undergo instantaneous gelation phase change. After overcoming the resistance of the one-way grout outlet valve, they are split and injected into the soil layer. This rheological mutation mechanism improves the retention rate of the grout in a dynamic water environment, reduces the scouring and dilution effect of groundwater flow on the grout, and ensures the compaction and cementation effect of the grout on the surrounding soft soil.
[0054] 3. The pavement surface layer of this invention adopts steel fiber reinforced concrete material with a customized high-polymer early-strength anti-mud water-reducing agent. The sulfonic acid groups inserted into the molecular structure of the water-reducing agent can inhibit the adsorption and intercalation of effective polymer molecules by soil minerals through electrostatic repulsion, maintaining the slump and workability of the concrete mixture under harsh mud-containing interference conditions. At the same time, the triethanolamine component in the water-reducing agent accelerates the nucleation reaction of early cement hydration products. Combined with the mechanical interweaving effect of steel fibers in the matrix, it enables the pavement pouring layer to quickly form early compressive strength that meets the traffic opening standard within a few hours, shortening the road closure and repair cycle. Attached Figure Description
[0055] Figure 1 The infrared spectral discrete characteristic data diagram and the GPC molecular weight distribution discrete curve diagram are shown in Test Example 1 of the present invention.
[0056] Figure 2 The apparent viscosity shear thinning curve and dynamic gelation time-viscosity abrupt change curve are shown in Test Example 2 of this invention.
[0057] Figure 3 The graphs show the discrete curves of the hydration heat release rate and the cumulative hydration heat release in Test Example 3 of this invention.
[0058] Figure 4 The bar charts for the dynamic water retention rate and the bar charts for the unconfined compressive strength at 3 days and 28 days are for Test Example 4 of this invention.
[0059] Figure 5The following are bar charts showing the initial and 1-hour slump, and the 4-hour and 24-hour compressive strength of Test Example 5 of this invention.
[0060] Figure 6 The graphs show the cumulative vertical settlement time curve and the 90-day deep horizontal displacement distribution curve for Test Example 6 of this invention. Detailed Implementation
[0061] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0062] Preparation Example 1:
[0063] This preparation example provides a method for preparing a polymeric early-strength anti-mud water-reducing agent, including the following steps:
[0064] Preparation of initial reaction base solution: 100.0g of isopentenyl alcohol polyoxyethylene ether was added to a reactor equipped with a constant temperature water bath jacket and a mechanical stirrer. 80.0g of deionized water was added, the mechanical stirrer was turned on, the stirring speed was set to 60rpm, the temperature was raised to 60℃, and the temperature was maintained until the macromonomer was completely dissolved to obtain the initial reaction base solution.
[0065] Dropwise copolymerization reaction: 8.0 g of acrylic acid and 3.0 g of 2-acrylamido-2-methylpropanesulfonic acid were dissolved in 30.0 g of deionized water to prepare solution A; 1.0 g of ammonium persulfate and 0.3 g of mercaptopropionic acid were dissolved in 30.0 g of deionized water to prepare solution B. Under constant temperature of 60℃ and continuous stirring, solutions A and B were simultaneously and uniformly added dropwise to the above reaction vessel using a metering pump, with the dropwise addition time of solution A controlled at 150 min and the dropwise addition time of solution B controlled at 180 min.
[0066] Incubation and maturation stage: After both solutions A and B have been added, continue to incubate and mature at a constant temperature of 60℃ for 60 minutes.
[0067] Compound modification and neutralization: Cool the reactor to 35°C, add 2.0g of triethanolamine, and react for 30min under continuous stirring. Then slowly add 30.0wt% sodium hydroxide aqueous solution to adjust the pH of the system to 6.0. Add deionized water to adjust the solid content to 40.0wt%. The high molecular weight early strength anti-mud water-reducing agent is obtained by discharging.
[0068] Preparation Example 2:
[0069] This preparation example provides a method for preparing a polymeric early-strength anti-mud water-reducing agent, including the following steps:
[0070] Preparation of initial reaction base solution: 100.0g of isopentenyl alcohol polyoxyethylene ether was added to a reactor equipped with a constant temperature water bath jacket and a mechanical stirrer. 80.0g of deionized water was added, the mechanical stirrer was turned on, the stirring speed was set to 75rpm, the temperature was raised to 63℃, and the temperature was maintained until the macromonomer was completely dissolved to obtain the initial reaction base solution.
[0071] Dropwise copolymerization reaction: Solution A was prepared by dissolving 10.0 g of acrylic acid and 4.5 g of 2-acrylamido-2-methylpropanesulfonic acid in 40.0 g of deionized water; Solution B was prepared by dissolving 1.25 g of ammonium persulfate and 0.45 g of mercaptopropionic acid in 40.0 g of deionized water. Under constant temperature of 63℃ and continuous stirring, Solutions A and B were simultaneously and uniformly added dropwise to the above reaction vessel using a metering pump. The dropping time for Solution A was controlled at 165 min, and the dropping time for Solution B was controlled at 195 min.
[0072] Incubation and curing stage: After both solutions A and B have been added, continue to incubate and cure at a constant temperature of 63℃ for 75 minutes.
[0073] Compound modification and neutralization: Cool the reactor to 35°C, add 3.0g of triethanolamine, and react for 30min under continuous stirring. Then slowly add 30.0wt% sodium hydroxide aqueous solution to adjust the pH of the system to 6.5. Add deionized water to adjust the solid content to 40.0wt%. The high molecular weight early strength anti-mud water-reducing agent is obtained by discharging.
[0074] Preparation Example 3:
[0075] This preparation example provides a method for preparing a polymeric early-strength anti-mud water-reducing agent, including the following steps:
[0076] Preparation of initial reaction base solution: Add 100.0g of isopentenyl alcohol polyoxyethylene ether to a reactor equipped with a constant temperature water bath jacket and a mechanical stirrer, add 80.0g of deionized water, turn on the mechanical stirrer, set the stirring speed to 90rpm, heat to 65℃, and maintain the temperature until the macromonomer is completely dissolved to obtain the initial reaction base solution.
[0077] Dropwise copolymerization reaction: 12.0 g of acrylic acid and 6.0 g of 2-acrylamido-2-methylpropanesulfonic acid were dissolved in 50.0 g of deionized water to prepare solution A; 1.5 g of ammonium persulfate and 0.6 g of mercaptopropionic acid were dissolved in 50.0 g of deionized water to prepare solution B. Under constant temperature of 65℃ and continuous stirring, solutions A and B were simultaneously and uniformly added dropwise to the above reaction vessel using a metering pump, with the dropwise addition time of solution A controlled at 180 min and the dropwise addition time of solution B controlled at 210 min.
[0078] Incubation and curing stage: After both solutions A and B have been added, continue incubation at a constant temperature of 65℃ for 90 minutes.
[0079] Compound modification and neutralization: The reaction vessel was cooled to 35°C, 4.0g of triethanolamine was added, and the reaction was carried out for 30min under continuous stirring. Then, a sodium hydroxide aqueous solution with a mass fraction of 30.0wt% was slowly added dropwise to adjust the pH value of the system to 7.0. Deionized water was added to adjust the solid content to 40.0wt%. The high molecular weight early strength anti-mud water-reducing agent was obtained by discharging the material.
[0080] Preparation Example 4:
[0081] This preparation example provides a method for preparing a polymeric early-strength anti-mud water-reducing agent, including the following steps:
[0082] Preparation of initial reaction base solution: Add 100.0g of isopentenyl alcohol polyoxyethylene ether to a reactor equipped with a constant temperature water bath jacket and a mechanical stirrer, add 80.0g of deionized water, turn on the mechanical stirrer, set the stirring speed to 75rpm, raise the temperature to 65℃, and maintain the temperature until the macromonomer is completely dissolved to obtain the initial reaction base solution.
[0083] Dropwise copolymerization reaction: Solution A was prepared by dissolving 10.0 g of acrylic acid and 4.5 g of 2-acrylamido-2-methylpropanesulfonic acid in 40.0 g of deionized water; Solution B was prepared by dissolving 1.25 g of ammonium persulfate and 0.45 g of mercaptopropionic acid in 40.0 g of deionized water. Under constant temperature (65℃) and continuous stirring, Solutions A and B were simultaneously and uniformly added dropwise to the above reaction vessel using a metering pump. The dropwise addition time for Solution A was controlled at 150 min, and the dropwise addition time for Solution B was controlled at 180 min.
[0084] Incubation and curing stage: After both solutions A and B have been added, continue incubation at a constant temperature of 65℃ for 90 minutes.
[0085] Compound modification and neutralization: The reactor was cooled to 35°C, 3.0g of triethanolamine was added, and the reaction was carried out for 30min under continuous stirring. Then, a sodium hydroxide aqueous solution with a mass fraction of 30.0wt% was slowly added dropwise to adjust the pH value of the system to 6.0. Deionized water was added to adjust the solid content to 40.0wt%. The high molecular weight early strength anti-mud water-reducing agent was obtained by discharging the material.
[0086] Example 1:
[0087] This embodiment provides a rapid reinforcement and anti-skid construction process for soft soil foundations, including the following steps:
[0088] Precise damage assessment and removal of damaged pavement: Ground-penetrating radar and portable dynamic penetrometers were used to detect damaged road sections, define the depth and extent of the weak layer, and mark the boundaries on the road surface. A hydraulic circular saw was used to cut along the boundaries, and a miniature cold milling machine was used to mill the old pavement structural layer with a thickness of 0.6m in layers. Milling waste was simultaneously loaded onto trucks and transported away, exposing the soft soil foundation.
[0089] Fabrication and Installation of Integrated Drainage and Grouting Micropile Pipes: Prefabricated integrated micropile pipes are constructed from an inner and outer pipe coaxially fitted together, with a closed, conical bottom. The lower 3.0m of the pipe body is the drainage section. The outer pipe wall has 8mm diameter quincunx-shaped perforations, and the interior of the outer pipe is filled with coarse sand filter material and wrapped with high-strength geotextile. The upper part of the pipe body is the grouting section. The outer pipe wall has 10mm diameter perforations, each covered with a one-way rubber sleeve valve. The annular space between the inner and outer pipes forms the A-component grout delivery channel, and the inner cavity of the inner pipe forms the B-component grout delivery channel. The two channels converge at the mixing chamber at the grout outlet of the grouting section.
[0090] Sequential installation of piles and active drainage: Piles are arranged in a spatial matrix with a vertical pile spacing of 1.5m × 1.5m, interspersed with inclined piles. The installation angle of the inclined piles is 60° to the horizontal plane, and they all point in the direction of lateral slippage of the roadbed. A high-frequency hydraulic vibratory pile driver is used to drive all micropiles into the soil, so that the pile bottom penetrates the silt layer and embeds into the bearing layer by 0.5m. After installation, the piles are left to stand for 2 hours. The excess pore water pressure generated by the compression of the soft soil layer drives the free water to be drained through the drainage section.
[0091] High-pressure dual-channel grouting forms a reinforced and consolidated body: High-pressure air is introduced into the two channels of the pile pipe to drain accumulated water. Then, the two pipelines of the high-pressure dual-liquid grouting system are connected to channels A and B respectively. The raw materials for component A grout, by mass fraction, include: 100 parts ultrafine silicate cement, 100 parts deionized water, 3.5 parts sodium bentonite, and 0.85 parts sodium polynaphthalene sulfonate, prepared by mixing at 1800 rpm for 20 minutes using a high-shear dispersion emulsifier; component B grout is liquid sodium silicate diluted with water to 34 Be'. Components A and B are pumped independently at a volume ratio of 1:1, with the pumping pressure set at 25 MPa. After the two grouts meet in the mixing chamber, they are instantly injected into the soil, overcoming the opening threshold pressure of the rubber sleeve valve, resulting in a splitting, compaction, and cementing composite effect. Grouting is stopped when the grouting pressure reaches 25 MPa and stabilizes for 10 seconds.
[0092] Laying reinforced subbase and rapid road restoration: Clean the top of the pile pipes and tighten the disc-shaped steel anchor heads. Spread and compact a 10cm thick layer of graded crushed stone, then lay biaxially oriented HDPE geogrid and galvanized welded steel mesh in sequence, using U-shaped clips to bind and lock the steel mesh to the steel anchor heads. Subsequently, spread, vibrate, and pour a 50cm thick layer of early-strength steel fiber reinforced concrete. The raw material ratio per cubic meter of this concrete is: 450kg of P.O42.5 grade ordinary Portland cement, 1080kg of coarse aggregate, 680kg of fine aggregate, 38kg of hook-shaped galvanized steel fiber, 1.5kg of the high-molecular-weight early-strength anti-mud water-reducing agent obtained in Preparation Example 2 (based on dry solids content), and 150kg of mixing water. Cover the surface with a curing film for curing.
[0093] Example 2:
[0094] This embodiment provides a rapid reinforcement and anti-skid construction process for soft soil foundations, including the following steps:
[0095] Precise damage assessment and removal of damaged pavement: Ground-penetrating radar and portable dynamic penetrometers were used to detect damaged road sections, define the depth and extent of the weak layer, and mark the boundaries on the road surface. A hydraulic circular saw was used to cut along the boundaries, and a miniature cold milling machine was used to mill the old pavement structural layer with a thickness of 0.6m in layers. Milling waste was simultaneously loaded onto trucks and transported away, exposing the soft soil foundation.
[0096] Fabrication and installation of integrated drainage and grouting micropile pipes: The structure of the micropile pipes is the same as in Example 1.
[0097] Sequential installation and active drainage of the micropiles: Piles are arranged in a spatial matrix with a vertical spacing of 1.5m × 1.5m, interspersed with inclined piles. The inclined piles are installed at a 45° angle to the horizontal plane and uniformly point in the direction of lateral slippage of the roadbed. A high-frequency hydraulic vibratory pile driver is used to drive all micropiles into the soil, ensuring the pile bottom penetrates the silt layer and embeds 0.5m into the bearing layer. After installation, the piles are left to stand for 2 hours to drain free water from the soil.
[0098] High-pressure dual-channel grouting forms a reinforced and consolidated body: High-pressure air is introduced into the two channels of the pile pipe to drain accumulated water. Then, the two pipelines of the high-pressure dual-liquid grouting system are connected to channels A and B respectively. The raw materials for component A grout, by mass fraction, include: 100 parts ultrafine silicate cement, 80 parts deionized water, 2.0 parts sodium bentonite, and 0.5 parts sodium polynaphthalene sulfonate, prepared by mixing at 1500 rpm for 15 minutes using a high-shear dispersion emulsifier; component B grout is liquid sodium silicate diluted with water to 30 Be'. Components A and B are pumped independently at a volume ratio of 1:0.8, with the pumping pressure set at 20 MPa. After the two grouts meet in the mixing chamber, they are instantly injected into the soil, overcoming the opening threshold pressure of the rubber sleeve valve. Grouting is stopped when the grouting pressure reaches 20 MPa and stabilizes for 10 seconds.
[0099] Laying reinforced subbase and rapid road restoration: Clean the top of the pile pipes and tighten the disc-shaped steel anchor heads. Spread and compact a 10cm thick layer of graded crushed stone, then lay biaxially stretched HDPE geogrid and galvanized welded steel mesh in sequence, using U-shaped clips to bind and lock the steel mesh to the steel anchor heads. Subsequently, spread, vibrate, and pour a 50cm thick layer of early-strength steel fiber reinforced concrete. The raw material ratio per cubic meter of this concrete is: 420kg of P.O42.5 grade ordinary Portland cement, 1050kg of coarse aggregate, 650kg of fine aggregate, 30kg of hook-type galvanized steel fiber, 1.2kg of the high-molecular-weight early-strength anti-mud water-reducing agent obtained in Preparation Example 1 (based on dry solids content), and 140kg of mixing water. Cover the surface with a curing film for curing.
[0100] Example 3:
[0101] This embodiment provides a rapid reinforcement and anti-skid construction process for soft soil foundations, including the following steps:
[0102] Precise damage assessment and removal of damaged pavement: Ground-penetrating radar and portable dynamic penetrometers were used to detect damaged road sections, define the depth and extent of the weak layer, and mark the boundaries on the road surface. A hydraulic circular saw was used to cut along the boundaries, and a miniature cold milling machine was used to mill the old pavement structural layer with a thickness of 0.6m in layers. Milling waste was simultaneously loaded onto trucks and transported away, exposing the soft soil foundation.
[0103] Fabrication and installation of integrated drainage and grouting micropile pipes: The structure of the micropile pipes is the same as in Example 1.
[0104] Sequential installation and active drainage of micropiles: Piles are arranged in a spatial matrix with a vertical spacing of 1.5m × 1.5m, interspersed with inclined piles. The inclined piles are installed at a 70° angle to the horizontal plane and uniformly point in the direction of lateral slippage of the roadbed. A high-frequency hydraulic vibratory pile driver is used to drive all micropiles into the soil, ensuring the pile bottom penetrates the silt layer and embeds 0.5m into the bearing layer. After installation, the piles are left to stand for 2 hours to drain free water from the soil.
[0105] High-pressure dual-channel grouting forms a reinforced and consolidated body: High-pressure air is introduced into the two channels of the pile pipe to drain accumulated water. Then, the two pipelines of the high-pressure dual-liquid grouting system are connected to channels A and B respectively. The raw materials for component A grout, by mass fraction, include: 100 parts ultrafine silicate cement, 120 parts deionized water, 5.0 parts sodium bentonite, and 1.2 parts sodium polynaphthalene sulfonate, prepared by mixing at 2000 rpm for 25 minutes using a high-shear dispersion emulsifier; component B grout is liquid sodium silicate diluted with water to 38Be'. Components A and B are pumped independently at a volume ratio of 1:1.2, with the pumping pressure set at 30 MPa. After the two grouts meet in the mixing chamber, they are instantly injected into the soil, overcoming the opening threshold pressure of the rubber sleeve valve. Grouting is stopped when the grouting pressure reaches 30 MPa and stabilizes for 10 seconds.
[0106] Laying reinforced subbase and rapid road restoration: Clean the top of the pile pipes and tighten the disc-shaped steel anchor heads. Spread and compact a 10cm thick layer of graded crushed stone, then lay biaxially stretched HDPE geogrid and galvanized welded steel mesh in sequence, using U-shaped clips to bind and lock the steel mesh to the steel anchor heads. Subsequently, spread, vibrate, and pour a 50cm thick layer of early-strength steel fiber reinforced concrete. The raw material ratio per cubic meter of this concrete is: 480kg of P.O42.5 grade ordinary Portland cement, 1100kg of coarse aggregate, 700kg of fine aggregate, 45kg of hook-type galvanized steel fiber, 1.8kg of the high-molecular-weight early-strength anti-mud water-reducing agent obtained in Preparation Example 3, and 160kg of mixing water. Cover the surface with a curing film for curing.
[0107] Comparative Example 1:
[0108] Compared with Example 1, the difference is that the traditional replacement and riprap method is used for soft soil treatment. Specifically, after the soft soil layer is excavated, riprap is dumped and compacted by its own weight. A conventional crushed stone cushion layer is laid on top and ordinary concrete pavement is poured. The rest is the same.
[0109] Comparative Example 2:
[0110] Compared with Example 1, the difference is that in the sequential implantation of the pile pipes and the active drainage steps, there are no inclined piles at 60° to the horizontal plane. Instead, the same number of micro pile pipes are all vertically implanted into the soil, that is, only the pure vertical pile group matrix is retained, and the rest are the same.
[0111] Comparative Example 3:
[0112] Compared with Example 1, the difference is that the traditional single-channel grouting pipe is used in the fabrication and installation steps of the integrated drainage and grouting micro-pile pipe; the B component grout is not used in the high-pressure dual-channel grouting to form a reinforced and consolidated body step, and only the A component grout is pumped through a single channel, while the rest are the same.
[0113] Comparative Example 4:
[0114] Compared with Example 1, the difference is that when preparing early-strength steel fiber concrete in the steps of laying the reinforced subbase and rapid road restoration, the polymeric early-strength anti-mud water-reducing agent obtained in Example 2 is replaced in equal amounts with commercially available conventional general-purpose polycarboxylate water-reducing agent, and all other aspects are the same.
[0115] Test Example 1:
[0116] This test example provides a characterization experiment on the molecular structure and molecular weight distribution of polymeric additives, used to verify the chemical structure design and polymerization reaction control effect of the polymeric early-strength anti-mud water-reducing agents obtained in Preparation Examples 1-4. A commercially available general-purpose polycarboxylate water-reducing agent used in Comparative Example 4 is used as a control sample. The experimental steps are as follows:
[0117] Preparation and testing of samples for infrared spectroscopy characterization: 50 mL of each of the polymeric early-strength anti-mud water-reducing agent obtained in Preparation Examples 1-4 and the sample obtained in Comparative Example 4 were placed in a vacuum drying oven at 60℃ and dried for 24 h. After grinding, solid powder samples were obtained. 1.5 mg of each of the above solid powder samples was weighed and thoroughly ground and mixed with 150 mg of spectroscopically pure potassium bromide powder dried at 200℃ in an agate mortar. The mixture was then pressed into uniform, transparent micro-sheets using a hydraulic tablet press under a pressure of 10 MPa. Fourier transform infrared spectroscopy was used to test each micro-sheet, with a scanning range set to 4000 cm⁻¹. -1 ~400cm -1 The resolution is 4cm. -1 The infrared absorption spectrum of each sample was recorded 32 times.
[0118] Preparation and testing of gel permeation chromatography samples: Accurately weigh 25.0 mg each of the dried powder samples from Preparation Examples 1-4 and Comparative Example 4, place them in 10 mL volumetric flasks, and dilute to volume with 0.1 mol / L sodium nitrate aqueous solution. Disperse the solutions in an ultrasonic oscillator for 15 min to prepare a test solution with a concentration of 2.5 mg / mL. Filter each test solution through a 0.22 μm aqueous polyethersulfone microporous membrane to remove potential small particles. Analyze the results using a gel permeation chromatograph equipped with a differential refractive index detector. The test column is a hydrophilic polymer matrix column in series. The mobile phase is 0.1 mol / L sodium nitrate aqueous solution, the flow rate is controlled at 1.0 mL / min, the column oven and detector temperatures are both set to 30 °C, and the injection volume is 50 μL. Column calibration is performed using monodisperse polyethylene glycol / polyethylene oxide standards. The molecular weight distribution curves of each group of samples are recorded, and the instrument workstation automatically calculates the weight-average molecular weight, number-average molecular weight, and polydispersity index.
[0119] Titration determination of double bond conversion rate: Take 5.0 g of each polymerization reaction solution from Preparation Example 1 to Preparation Example 4 and determine the double bond content of the residual macromonomer by bromine-carbon tetrachloride method. Calculate the double bond conversion rate of the polymerization reaction based on the amount of double bonds consumed before and after the reaction.
[0120] Based on the above measurements, the gel permeation chromatography data and conversion rate results for each sample are shown in Table 1.
[0121] Table 1. Gel permeation chromatography parameters and reaction conversion rate data of polymeric auxiliaries
[0122] Sample Name Weight-average molecular weight (g / mol) Number-average molecular weight (g / mol) Multi-dispersion index Double bond conversion rate (wt%) Preparation Example 1 30214 26738 1.130 96.8 Preparation Example 2 36412 32395 1.124 98.2 Preparation Example 3 44896 38871 1.155 97.5 Preparation Example 4 36805 32144 1.145 97.9 Comparative Example 4 68420 44142 1.550 91.4
[0123] Summary: Based on Figure 1Based on the test data and spectral characteristics in Table 1, the following analytical results are obtained regarding the structure and properties of each sample:
[0124] The products obtained from Preparation Examples 1-4 were subjected to a temperature of 3400 cm⁻¹. -1 The vicinity exhibits a large characteristic peak of hydroxyl stretching vibration, at 2880 cm⁻¹. -1 A distinct stretching vibration peak of methyl and methylene groups appears at 1720 cm⁻¹. -1 The nearby absorption peak corresponds to the carbonyl stretching vibration of the unsaturated carboxyl group in acrylic acid, 1100 cm⁻¹. -1 The nearby broad and strong absorption peaks are attributed to the asymmetric stretching vibrations of the polyether side chains in isopentenyl alcohol polyoxyethylene ether. In addition to the common peaks mentioned above, Preparation Examples 1 to 4 show peaks at 1180 cm⁻¹. -1 and 1040cm -1 Clear characteristic peaks of asymmetric and symmetric stretching vibrations of sulfonic acid groups were observed at 625 cm⁻¹. -1 The stretching vibration peak of the CS bond was also observed, while no strong sulfonic acid characteristic peak group was detected in the spectrum of the commercially available ordinary polycarboxylate superplasticizer in Comparative Example 4, proving that the 2-acrylamido-2-methylpropanesulfonic acid monomer has participated in the copolymerization reaction, and its unique anti-mud adsorption functional group has been successfully grafted into the polymer backbone.
[0125] Preparation Examples 1-4, through the control of chain transfer agent dosage and dropping process parameters, achieved a double bond conversion rate of over 96.8 wt%, with the weight-average molecular weight of the product remaining within the range of 30214 g / mol to 44896 g / mol. The chromatographic elution curves showed a symmetrical single-peak distribution, and the polydispersity index was concentrated between 1.124 and 1.155. In contrast, the polydispersity index of the product in Comparative Example 4 was as high as 1.550, and a wide low-molecular-weight tail region was present on the right side of the chromatographic curve, reflecting numerous local side reactions and significant differences in molecular chain length during the reaction process. Preparation Example 2, due to the use of a moderate ratio and stepwise temperature control, reduced the polydispersity index to 1.124, exhibiting a concentrated molecular weight distribution. The concentrated and uniform molecular weight distribution and high functional group density ensure the stable adsorption of the auxiliary agent molecules on the surface of the hydrated particles and the utilization of steric hindrance, providing material support for the subsequent establishment of the early mechanical framework.
[0126] Test Example 2:
[0127] This test example provides experimental results on the rheological properties and gelation kinetics of grout, used to verify the fluid phase change characteristics of the dual-channel grouting systems of Examples 1-3 before and after mixing, with the single-component pure cement grout system in Comparative Example 3 as a comparison object. The experimental steps are as follows:
[0128] Rheological property determination of single-component slurries: 50 mL each of the slurries of component A prepared in Examples 1-3 and the pure cement slurry prepared in Comparative Example 3 were placed in a constant temperature water bath and adjusted to 20°C. Steady-state shear tests were performed on each sample using a rotational rheometer equipped with a coaxial cylinder testing system. During the test, the shear rate increased from 0.1 s⁻¹. -1 linearly increased to 100s -1 The instrument automatically collects shear stress and apparent viscosity data at the corresponding shear rate.
[0129] Two-component gel time determination: Based on the volume ratio of component A to component B set in each embodiment, the two component slurries were simultaneously injected into a mixing container equipped with an electromagnetic stirrer using a dual-pump injection system. Timing began from the moment of mixing and contact. The inverted cup method was used to observe the loss of fluidity of the mixed slurry; the initial setting time was recorded when the slurry stopped flowing at a 45° tilt. Subsequently, the sample was moved to the Vicat apparatus platform, and the final setting time was recorded when the standard needle sank to a depth of no more than 1 mm. For Comparative Example 3, component B was not added to the sample; the gel time of pure component A was measured directly. Each group of samples was tested three times, and the arithmetic mean was taken.
[0130] Dynamic rheological monitoring of the gelation process: The rheometer system was set to constant small amplitude shear mode, and the constant shear rate was set to 1.0 s⁻¹. -1 Liquid A and liquid B were simultaneously injected in the corresponding proportions of each embodiment using an in-situ mixing attachment. The instrument continuously recorded the apparent viscosity change curve over time, with the test time window set to 0–60 s. Comparative Example 3 involved injecting only a single-component pure cement slurry and monitoring its viscosity over the same period of time.
[0131] Based on the above measurements, the initial viscosity of each component and the gelation time after mixing are shown in Table 2.
[0132] Table 2. Results of slurry rheological parameters and gel time measurements for each group.
[0133] Sample Name Initial apparent viscosity of component A (mPa·s) Initial setting time (s) Final setting time (s) Example 1 145.2 22.8 31.4 Example 2 182.6 34.1 42.7 Example 3 112.4 16.5 24.9 Comparative Example 3 155.8 21450 27680
[0134] Summary: Based on Figure 2 Based on the test data and rheological behavior characteristics in Table 2, the following experimental verification conclusions are reached regarding the dual-channel transient gelation mechanism of this invention:
[0135] The suspensions of component A prepared in Examples 1-3 were processed in 0.1 s. -1 ~100s -1Within the shear rate range, it exhibits typical shear-thinning non-Newtonian fluid characteristics. The initial apparent viscosity of each embodiment ranges from 112.4 mPa·s to 182.6 mPa·s, indicating that after adding the bentonite and water-reducing agent system of the present invention, the suspension system has a certain structural viscosity in the static state to prevent solid phase sedimentation, while the viscosity decreases significantly under transport shearing, meeting the pumping fluidity requirements of high-pressure grouting.
[0136] The slurries in Examples 1-3 maintained a low basic viscosity for the first ten seconds after mixing and contact, ensuring the slurry's penetration and diffusion into the soil pores. Subsequently, the viscosity curve exhibited an exponential jump near the initial setting time, with the apparent viscosity of the system exceeding 10 within a few seconds. 6 The viscosity of the two-component grout, measured in mPa·s, exhibits an instantaneous phase transition from liquid to solid. In Example 3, with a high water-cement ratio, increasing the proportion of the two components and the Baume degree of the water glass advanced the initial setting time to 16.5 s, reflecting the accelerated cross-linking reaction of the calcium silicate gel network during cement hydration after activation by a strong alkali. In Comparative Example 3, lacking the chemical activation of component B water glass, the viscosity remained level within the test window, resulting in a macroscopic initial setting time as long as 21450 s. These differences confirm that the consolidation reaction triggered by the instantaneous contact of the two-component grout through the micro-pile bottom mixing chamber can overcome the dilution effect in groundwater environments and solve the problem of high loss rate in traditional single-component cement grouting.
[0137] Test Example 3:
[0138] This test example provides a microcalorimetric test experiment on the exothermic kinetics of cement hydration to verify the micro-regulatory effect of the polymeric early-strength anti-mud water-reducing agents obtained in Preparation Examples 1-3 on the early hydration process of cement. The commercially available general-purpose polycarboxylate water-reducing agent used in Comparative Example 4 is used as a control. The experimental steps are as follows:
[0139] Preparation of cement paste test samples: Weigh 50.0g of P.O42.5 grade ordinary Portland cement and 16.5g of deionized water at a water-cement ratio of 0.33. Dissolve the high-molecular-weight early-strength anti-mud water-reducing agent obtained in Preparation Examples 1-3 (with a dry solids content of 0.15g) and the commercially available conventional water-reducing agent used in Comparative Example 4 in the deionized water. Mix the solution containing the water-reducing agent and the cement powder in a constant-temperature high-speed cement paste mixer. First, stir at low speed for 120s, stop for 15s, and then stir at high speed for 120s to obtain a homogeneous cement paste sample.
[0140] Isothermal hydration heat release rate and cumulative heat release test: Accurately weigh 3.0g of each of the above-mentioned mixed cement paste samples and place them into pre-calibrated standard glass ampoules. After sealing, quickly place them in the test channel of an eight-channel isothermal microcalorimeter that has been constant-temperatured to 20℃. An ampoule containing deionized water of equal mass specific heat capacity is used as the reference channel.
[0141] Data Acquisition and Processing: Start the data acquisition program of the micro calorimeter to continuously monitor and record the hydration heat release data within 0–24 h. The instrument workstation automatically subtracts baseline drift and outputs the hydration heat release rate curve and cumulative hydration heat release curve normalized to per gram of cementitious material for each sample, and extracts the induction period end time, hydration heat release peak time, and peak heat release rate parameters.
[0142] Based on the above measurements, the early hydration exothermic kinetic characteristic parameters of each sample are shown in Table 3.
[0143] Table 3. Hydration exothermic kinetic parameters of samples in each group
[0144] Sample Name End time of induction period (h) Main hydration exothermic peak time (h) Peak heat release rate (mW / g) Cumulative heat release over 24 hours (J / g) Preparation Example 1 1.15 5.82 3.42 185.3 Preparation Example 2 1.28 5.95 3.35 181.6 Preparation Example 3 1.08 5.61 3.58 189.2 Comparative Example 4 2.85 8.74 2.75 142.8
[0145] Summary: Based on Figure 3 Based on the test data and hydration exothermic kinetic curve characteristics in Table 3, the following analytical results are obtained regarding the early microscopic regulation mechanism of the additive of this invention:
[0146] The cement paste samples with added water-reducing agents from Preparation Examples 1-3 showed that the hydration induction period ended between 1.08 h and 1.28 h, and the main hydration exothermic peak appeared between 5.61 h and 5.95 h. In Comparative Example 4, the sample with added commercially available conventional polycarboxylate superplasticizer showed an extended induction period of 2.85 h, a delayed main hydration exothermic peak appearance at 8.74 h, and a decrease in the peak exothermic rate from over 3.35 mW / g in the Preparation Examples to 2.75 mW / g. This difference in exothermic characteristics reflects the microscopic regulatory role played by the triethanolamine groups grafted into the molecular structure of the additives in the Preparation Examples during the early stages of cement hydration. Triethanolamine can complex aluminum ions in the liquid phase, lowering the thermodynamic energy barrier for ettringite crystal nucleation and promoting a rapid acceleration phase in the early stages of hydration.
[0147] The cumulative heat release over 24 hours for samples from Preparation Examples 1 to 3 reached 181.6 J / g to 189.2 J / g, higher than the 142.8 J / g of Comparative Example 4. The increase in early hydration heat release corresponds to the increase in the amount of hydration products generated. The dense hydrated calcium silicate gel and the ettringite crystal network intertwine with each other in a short period of time, providing a materials science basis for the establishment of the early mechanical skeleton of concrete after pouring on a macroscopic scale.
[0148] Test Example 4:
[0149] This test example provides experiments to determine the slurry erosion resistance retention rate and the mechanical properties of the consolidated body in a water-rich and dynamic environment. It is used to verify the film-forming and consolidation effect of the high-pressure dual-channel grouting process in Examples 1-3, and compares it with the traditional single-channel pure cement grouting process in Comparative Example 3. The experimental steps are as follows:
[0150] In a transparent acrylic test tank measuring 1.0m × 0.5m × 0.5m, pre-washed graded crushed stone aggregate with a porosity of 40% was piled up to simulate a large-pore, water-rich stratum. A circulating water pump was turned on, and the water flow velocity in the tank was adjusted and stabilized at 0.5m / s. Grout from Examples 1 to 3 and Comparative Example 3 were injected into the center of the crushed stone layer through a grouting pipe equipped with a pressure control device. The initial theoretical total injection volume for each group was set at 2000mL. After the grouting process, the tank was kept under dynamic water flushing for 30 minutes. Then, the water flow was stopped, and the free water in the tank was slowly drained. The formed grout-crushed stone solidified body was then removed as a whole. The total volume of the irregular solidified body was determined using the Archimedes' displacement method. After deducting the volume of the crushed stone aggregate contained within, the actual retained solidified grout volume was obtained. The dynamic water retention rate of the grout was calculated by comparing it with the initial injection volume.
[0151] The consolidated bodies formed by scouring in the previous step were wrapped with damp cloths and transferred to a standard curing room for curing at a temperature of 20±2℃ and a relative humidity of over 95%. Consolidated body samples were removed after 3 days and 28 days of curing, respectively. Irregular samples were cut and ground into standard cubic test specimens with a side length of 70.7 mm using a core cutter. The unconfined compressive strength of each specimen was determined using a computer-controlled electronic universal testing machine. The loading rate was set to 0.5 MPa / s, and the peak failure load was continuously recorded until the specimen failed, and then converted into the corresponding compressive strength value. Each test was performed in triplicate, and the arithmetic mean of the results was taken.
[0152] Based on the above experiments, the retention rate of slurry in each group under dynamic water scouring environment and the compressive strength of the consolidated body at each age are shown in Table 4.
[0153] Table 4. Data on dynamic water retention rate and mechanical properties of solidified bodies in grouting systems of each group.
[0154] Sample Name Slurry retention rate (vol%) after water scouring 3-day unconfined compressive strength (MPa) 28-day unconfined compressive strength (MPa) Example 1 92.4 12.3 21.6 Example 2 89.1 9.8 18.2 Example 3 95.8 15.6 25.4 Comparative Example 3 16.5 0.9 1.4
[0155] Summary: Based on Figure 4 Based on the measurement data in Table 4, the following experimental verification conclusions are reached regarding the synergistic consolidation mechanism of fluid mechanics and chemical kinetics:
[0156] In Examples 1-3, under a 0.5 m / s dynamic water flow, the slurry retention rate remained between 89.1 vol% and 95.8 vol%, and the solidified body maintained its complete structural morphology. In Comparative Example 3, the retention rate of pure cement slurry under the same conditions was only 16.5 vol%, with most of the slurry being lost and dispersed with the water flow. This difference reflects that after the dual-channel micropile pipe achieves high-pressure turbulent mixing in the confined underground space, the instantaneous chemical activation of the ultrafine cement by the water glass promotes instantaneous gelation of the system. The resulting calcium silicate gel network, possessing a certain initial structural strength, encapsulates and bonds the surrounding strata skeleton before being destroyed by the shear force of the water flow, effectively resisting the dilution effect of external groundwater.
[0157] The solidified bodies formed in Examples 1-3 exhibited a 3-day compressive strength of 9.8 MPa to 15.6 MPa and a 28-day compressive strength of 18.2 MPa to 25.4 MPa, providing the necessary bearing capacity for soft soil foundations used in roads. In Comparative Example 3, due to the absence of an instantaneous gel phase transition, the smaller amount of slurry remaining in the pores of the crushed stone resulted in lower strength after solidification, with a 28-day compressive strength of only 1.4 MPa. In the example systems, because the cement particles were not lost with water, the gel phase generated by the reaction of components A and B continued to densify during subsequent hydration, forming a continuous cemented force-transfer network between the crushed stone skeleton, verifying the effectiveness of this technical solution for deep consolidation and reinforcement of soft soil foundations.
[0158] Test Example 5:
[0159] This test example provides a comparative test experiment on the workability and early mechanical properties of concrete under mud-containing interference environment. It is used to verify the anti-mud adsorption capacity and rapid hardening and traffic performance of the early-strength steel fiber concrete prepared in Examples 1-3 under actual complex working conditions. The concrete in Comparative Example 4, in which the polymeric early-strength anti-mud water-reducing agent was replaced with an equal amount of commercially available conventional polycarboxylate water-reducing agent, is used as a comparison object. The experimental steps are as follows:
[0160] Preparation and workability monitoring of mud-containing test mixtures: Ordinary Portland cement, coarse and fine aggregates, galvanized steel fibers, water-reducing agent, and mixing water were weighed according to the concrete mix proportions required for Examples 1-3 and Comparative Example 4. To simulate the harsh working conditions of mud-containing aggregates in the field, 200-mesh spectrophotometric pure calcium-based montmorillonite powder was used to replace 5.0 wt% of the fine aggregates. The above materials were mixed using a forced-action horizontal concrete mixer. The dry materials were first mixed and stirred for 60 seconds, followed by the addition of mixing water containing the water-reducing agent and stirring for another 180 seconds to obtain the concrete mixtures for each group. Immediately, a portion of the mixture was placed into a standard slump cone in three layers. Each layer was tamped 25 times from the outside in using a tamping rod. The slump cone was then lifted vertically and smoothly, and the difference between the highest point of the concrete mixture and the height of the cone was measured using a steel ruler and recorded as the initial slump. Place the remaining mixture in a plastic box and cover it with a moisturizing film to allow it to stand for curing. When the timer reaches 60 minutes, pour the mixture back into the mixer and gently stir it again for 30 seconds. Measure the slump after 1 hour using the same steps and calculate the slump loss rate.
[0161] Determination of early and 24-hour compressive strength: Each mixture that had completed the initial workability test during the preparation and workability monitoring steps of the mud-containing test mixture was placed into a standard cast iron mold (150mm × 150mm × 150mm) and subjected to high-frequency vibration on a vibrating table. The molded molds were then transferred to a constant temperature chamber at 20±2℃ and covered with a thin film for static curing. Molds that had been molded for 4±0.1 hours were demolded, and their 4-hour early compressive strength was immediately measured using a computer-controlled electro-hydraulic servo universal testing machine. The remaining specimens were cured in a standard curing chamber at 20±2℃ and a relative humidity of not less than 95% for 24 hours, and their 24-hour compressive strength was measured. The loading process adopted a displacement-load combined control mode. The initial loading rate was set to 0.6 MPa / s, and loading continued until the specimen failed. The maximum failure load was continuously recorded. Three parallel specimens were tested for each mix proportion, and the arithmetic mean of the test results was calculated.
[0162] Based on the above experiments, the workability evolution of mud-containing concrete mixtures in each group and the mechanical strength data at different ages are shown in Table 5.
[0163] Table 5. Workability and early compressive strength data of concrete in mud-containing environments for each group
[0164] Sample Name Initial slump (mm) Slump (mm) after 1 hour Slump loss rate (%) 4-hour compressive strength (MPa) 24-hour compressive strength (MPa) Example 1 215 190 11.6 22.4 45.6 Example 2 205 182 11.2 20.1 42.3 Example 3 220 195 11.4 24.8 48.2 Comparative Example 4 185 95 48.6 8.6 28.4
[0165] Summary: Based on Figure 5 Based on the experimental test data in Table 5, the following conclusions can be drawn regarding the mechanism of action of polymeric additives in concrete under complex working conditions:
[0166] With the introduction of 5.0 wt% montmorillonite clay into the aggregate, the concrete mixtures prepared in Examples 1-3 achieved an initial slump of 205 mm to 220 mm, and the slump loss rate after standing for 1 hour was controlled within the range of 11.2% to 11.6%, maintaining good working fluidity above 180 mm. In Comparative Example 4, the sample using a commercially available general-purpose polycarboxylate superplasticizer showed an initial slump reduced to 185 mm, and after standing for 1 hour, severe agglomeration and rheological loss occurred, with a slump loss rate of 48.6%, failing to meet the requirements for subsequent on-site vibration paving. This comparative data confirms the microscopic barrier effect formed by the 2-acrylamido-2-methylpropanesulfonic acid monomer grafted into the polymer additive structure. The strong negative charge of the sulfonic acid group electrostatically repels the negative charge between the clay mineral layers, inhibiting the adsorption and intercalation of free polymer molecules by the clay, ensuring that effectively free polymer molecules continue to adsorb on the surface of cement particles and exert a steric hindrance dispersion effect.
[0167] The specimens in Examples 1-3 exhibited compressive strengths of 20.1 MPa to 24.8 MPa after 4 hours of curing, meeting the national standard's mechanical threshold for rapid reopening of roads after repair, typically requiring an early compressive strength of at least 20.0 MPa. After 24 hours of continued curing, the compressive strength increased to 42.3 MPa to 48.2 MPa. In contrast, the specimen in Comparative Example 4 showed a compressive strength of only 8.6 MPa after 4 hours of curing, highlighting its shortcomings in retarding and insufficient early strength. The experimental results demonstrate that the customized high-molecular-weight early-strength anti-mud water-reducing agent in the example formulation possesses both anti-mud and early-strength control properties. Even under conditions of low water-cement ratio and clay adsorption competition, the triethanolamine groups on the additive molecular chain effectively complex metal ions, accelerating the nucleation of hydration products and promoting the early construction of a high-strength steel fiber interwoven skeleton, ensuring the safe restoration of traffic in a short time after road repair.
[0168] Test Example 6:
[0169] This test example provides a macroscopic geotechnical mechanical performance monitoring experiment for large-scale three-dimensional composite foundations. It is used to verify the constraint effect of the vertical pile + 60° inclined pile spatial matrix in Example 1 on the settlement and lateral slippage of soft soil foundations. The traditional riprap replacement process in Comparative Example 1 and the pure vertical pile group process in Comparative Example 2 are used as comparison objects. The experimental steps are as follows:
[0170] Preparation of the large-scale physical model test trench: In a large reinforced concrete test trench measuring 10.0m × 6.0m × 5.0m (length × width × depth), a dense layer of sand and gravel with a thickness of 1.5m was filled and compacted layered from bottom to top as the relative bearing layer. Above the bearing layer, a 0.2m thick layer of polytetrafluoroethylene film mixed with bentonite slurry was laid at a 15° angle to simulate a potential weak sliding surface. High-moisture-content silty clay was then filled in layers above the sliding surface up to the design elevation to simulate the soft soil foundation environment in the field. The test trench was divided into three independent test sections.
[0171] Foundation reinforcement and monitoring instrument installation: In the three test sections, construction was carried out strictly according to the foundation treatment methods set in Example 1, Comparative Example 1, and Comparative Example 2. A surface settlement plate was pre-embedded at the geometric center of the composite foundation in each section, and inclinometer tubes with guide grooves were vertically drilled and embedded into the foundation. The bottom of the inclinometer tubes needed to penetrate at least 1.0m into the lower sand and gravel bearing layer and be anchored at the bottom to serve as a reference point for horizontal displacement testing. Early-strength steel fiber reinforced concrete pavement was poured and cured on the foundation surface.
[0172] Dynamic loading and long-term monitoring: A rigid loading pad was laid on the foundation surface, and a cyclic dynamic load with a frequency of 2Hz and an amplitude of 50kN was applied using a large electro-hydraulic servo actuator to simulate the long-term fatigue disturbance caused by heavy traffic on actual roads. The loading process lasted for 90 days. On the 30th, 60th, and 90th days of the loading period, the cumulative vertical settlement of the settlement plate was read using a precision level. At the same time, a sliding high-precision inclinometer probe was used to collect data every 0.5m from bottom to top inside the inclinometer tube, recording the distribution of horizontal lateral displacement in the foundation depth direction, and extracting the maximum horizontal displacement.
[0173] Based on the above experiments, the settlement and lateral slip data of the model foundation in each test section are shown in Table 6.
[0174] Table 6. Deformation monitoring data of the foundation of each model group under cyclic dynamic loading
[0175] Sample Name Cumulative vertical settlement over 30 days (mm) Cumulative vertical settlement over 90 days (mm) Maximum lateral displacement over 90 days (mm) Depth of maximum lateral displacement (m) Example 1 8.4 12.7 3.5 3.5 Comparative Example 1 64.2 115.8 42.1 3.5 Comparative Example 2 11.6 18.2 26.8 3.5
[0176] Summary: Based on Figure 6 Based on the test data and soil displacement distribution characteristics in Table 6, the following experimental verification conclusions are reached regarding the active force-bearing mechanism of micro-piles with inclined anti-sliding:
[0177] Under continuous dynamic loading for 90 days, the traditional replacement and riprap method in Comparative Example 1 failed to effectively transfer the load to the deeper layers, and the large pores between the stones led to compaction and compression, resulting in a cumulative vertical settlement of 115.8 mm. In Example 1 and Comparative Example 2, through the replacement and bonding effect of micropiles, the surface traffic load was directly transferred across the soft soil layer to the bottom gravel bearing layer, with vertical settlement significantly controlled at 12.7 mm and 18.2 mm, respectively. This comparison reflects the effectiveness of vertical micropiles in suppressing uneven settlement and bearing heavy traffic loads.
[0178] At the simulated potential sliding surface (depth 3.5m), abrupt peak values of horizontal shear displacement were observed in all test sections. Comparative Example 2, despite possessing good vertical bearing capacity, exhibited limited shear stiffness under horizontal soil thrust due to the simple vertical pile group, resulting in a significant lateral slip of 26.8mm. Example 1 showed a maximum lateral displacement of only 3.5mm at the slip surface, approaching a stable state of zero. This mechanical characterization directly demonstrates that introducing 60° inclined piles precisely pointing in the slip direction into the pile group matrix, after penetrating the sliding surface and entering the bearing layer in the soil and rock medium, acts as a micro-foundation anchor, resisting pull-out and shear stresses. The inclined piles actively provide tensile and shear stresses opposite to the soil's sliding tendency, locking the lateral displacement freedom of the high-water-content soil and solving the overall slip instability problem of the roadbed under the influence of bias pressure and water-rich lateral seepage.
Claims
1. A rapid reinforcement and anti-skid construction process for soft road foundations, characterized in that, Includes the following steps: Detect damaged road sections, define the depth and extent of the weak layer, cut joints along the boundary and mill the old pavement structure layer in layers to expose the soft soil foundation; The prefabricated integrated drainage and grouting micro-pile pipe consists of an inner pipe and an outer pipe coaxially sleeved together. The lower part is the drainage section and the upper part is the grouting section. The annular space between the inner pipe and the outer pipe in the grouting section forms the A-component grout delivery channel, and the inner cavity of the inner pipe is the B-component grout delivery channel. The two channels converge in the mixing chamber at the grout outlet of the grouting section. Micropile tubes are implanted into the soft soil foundation to form a spatial matrix. The micropile tubes include vertical piles and inclined piles. The inclined piles are all pointed in the direction of lateral slippage of the roadbed. The bottom of the pile penetrates the silt layer and is embedded 0.5m into the bearing layer. After implantation, the piles are left to stand for 2 hours and the free water in the stratum is discharged through the drainage section. The A component slurry and the B component slurry are pumped to the A component slurry delivery channel and the B component slurry delivery channel respectively. After the two slurries meet in the mixing chamber, they are injected into the soil through a one-way rubber sleeve valve to form a reinforced and consolidated body. Clean the top of the pile pipe and tighten the disc-shaped steel anchor head. Spread and compact graded crushed stone, lay galvanized welded steel mesh and tie it to the steel anchor head and lock it in place. Then pour early-strength steel fiber concrete.
2. The rapid reinforcement and anti-skid construction process for soft soil foundations according to claim 1, characterized in that, The bottom of the micro-pile pipe is closed and conical. The lower 3.0m of the pipe body is the drainage section. The outer pipe wall of the drainage section has plum blossom-shaped holes with a diameter of 8mm. The inside of the outer pipe is filled with coarse sand filter material. The upper part of the pipe body is the grouting section. The outer pipe wall of the grouting section has grout outlet holes with a diameter of 10mm. Each grout outlet hole is covered with a one-way rubber sleeve valve.
3. The rapid reinforcement and anti-skid construction process for soft soil foundations according to claim 1, characterized in that, The piles are arranged in a spatial matrix with a vertical pile spacing of 1.5m × 1.5m. The inclined piles are interspersed among the vertical piles, and the insertion angle of the inclined piles is 45° to 70° with the horizontal plane.
4. The rapid reinforcement and anti-skid construction process for soft soil foundations according to claim 1, characterized in that, Before pumping the slurry, high-pressure air is introduced into the A-component slurry delivery channel and the B-component slurry delivery channel to drain the accumulated water; The A component grout and the B component grout are pumped independently at a volume ratio of 1:0.8 to 1:1.2, with the pumping pressure set at 20MPa to 30MPa. Grouting is stopped when the grouting pressure reaches the set pressure and stabilizes for 10 seconds.
5. The rapid reinforcement and anti-skid construction process for soft soil foundations according to claim 1, characterized in that, The raw materials for component A slurry, by mass parts, include: 100 parts of ultrafine silicate cement; 80-120 parts deionized water; Sodium-based bentonite 2.0-5.0 parts; Sodium polynaphthalene sulfonate 0.5-1.2 parts; It was prepared by mixing at 1500 rpm to 2000 rpm for 15 min to 25 min using a high-shear dispersing emulsifier; The B component slurry is liquid sodium silicate diluted with water to 30Be' to 38Be'.
6. The rapid reinforcement and anti-skid construction process for soft soil foundations according to claim 1, characterized in that, The raw material mix ratio for each cubic meter of the aforementioned early-strength steel fiber concrete is: P.O42.5 grade ordinary Portland cement 420~480kg; Coarse aggregate 1050~1100kg; Fine aggregate 650~700kg; 30-45 kg of hook-type galvanized steel fiber; High-molecular-weight early-strength anti-mud water-reducing agent: 1.2–1.5 kg; Mixing water: 140–160 kg; The weight of the polymeric early-strength anti-mud water-reducing agent is calculated based on its dry solids content.
7. The rapid reinforcement and anti-skid construction process for soft soil foundations according to claim 6, characterized in that, The raw materials of the polymeric early-strength anti-mud water-reducing agent include, by mass parts: 100 parts of isopentenyl alcohol polyoxyethylene ether; Acrylic acid 8.0-12.0 parts; 3.0-6.0 parts of 2-acrylamido-2-methylpropanesulfonic acid; 1.0-1.5 parts of ammonium persulfate; Mercaptopropionic acid 0.3-0.6 parts; Triethanolamine 2.0-4.0 parts.
8. The rapid reinforcement and anti-skid construction process for soft soil foundations according to claim 7, characterized in that, The high-molecular-weight early-strength anti-mud water-reducing agent is prepared through the following steps: Add 100 parts of isopentenyl alcohol polyoxyethylene ether and 80 parts of deionized water to a reaction vessel, and stir at 60℃~65℃ and 60rpm~90rpm until completely dissolved to obtain the initial reaction base liquid. Acrylic acid and 2-acrylamido-2-methylpropanesulfonic acid were dissolved in 30-50 parts of deionized water to prepare solution A, and ammonium persulfate and mercaptopropionic acid were dissolved in 30-50 parts of deionized water to prepare solution B. Solutions A and B were simultaneously and uniformly added dropwise at 60℃~65℃ with continuous stirring. The dropwise addition time of solution A was 150min~180min, and the dropwise addition time of solution B was 180min~210min. After both solutions A and B have been added, keep the mixture warm for 60 to 90 minutes to allow it to mature. Cool to 35°C, add triethanolamine and react for 30 min with continuous stirring. Slowly add 30.0 wt% sodium hydroxide aqueous solution to adjust the pH to 6.0-7.0, and add deionized water to adjust the solid content to 40.0 wt%.
9. The rapid reinforcement and anti-skid construction process for soft soil foundations according to claim 1, characterized in that, The process of spreading and compacting graded crushed stone, laying galvanized welded steel mesh and securing it with steel anchor heads specifically includes: Spread and compact 10cm thick graded crushed stone, then lay biaxially stretched HDPE geogrid and galvanized welded steel mesh in sequence, and use U-shaped clips to tie and lock the galvanized welded steel mesh to the disc-shaped steel anchor head.
10. The construction process for rapid reinforcement and anti-skid treatment of soft soil foundations according to claim 1, characterized in that, The process of detecting road defects involves defining the depth and extent of the weak layer, cutting joints along the boundaries, and milling the old pavement structure layer in layers. Specifically, this includes: Ground penetrating radar and portable dynamic penetrating probes were used to detect the damaged road sections, define the depth and extent of the weak layer, and mark the boundaries on the road surface. A hydraulic circular saw was used to cut along the boundary, and a mini cold milling machine was used to mill the old pavement structure layer with a thickness of 0.6m in layers.
